Kesehatan Sendi Optimal : Edukasi Osteoarthritis Bagi Lansia di Desa Gedongan - Oktaviani Fitriyah; Aan Sofyan; Wachidah Yuniartika; Daris Trigamadia; Aulai Rahman; Nikmah Nurul Utami; Charisma Alzura; Mohammad Rizqi; Diny Oktri Sani; Anindya Suryawati; Verent Vidanindya Ivena; Gita Febri Cahyani; Arvita Ningtyas (Journal of Student Research, 2024)
Osteoarthritis is a cartilage disorder in the joints of bones that often affects elderly people. As many as 24 million people in the Southeast Asia region and 151 million people worldwide suffer from osteoarthritis. The community service practice aims to provide education to elderly people with osteoarthritis. The sampling technique was purposive sampling with 85 elderly respondents. The level of knowledge of the elderly about osteoarthritis disease is obtained through pretest and posttest. Providing education to the elderly about osteoarthritis disease by counseling and exposure to material using posters and leaflets and demonstrations related to the handling of osteoarthritis. Analysis of research data using chi square and fisher exact tests. The results obtained in the age factor (p = 0.021), gender (p = 0.015), BMI (p = 0.002) and physical activity (p = 0.584). There is a relationship between age, gender and body mass index with the incidence of osteoarthritis in the elderly and there is no relationship between physical activity and the incidence of osteoarthritis in the elderly.